Internationalisation and innovation on balanced scorecard (BSC) among Malaysian small and medium enterprises - Poh, Ling Chong; Tze, San Ong; Abdullah, Amalina; Wei, Chong Choo (Growing Science, 2019)
The purpose of this paper is to identify the relationship between the determinants of internationalisation and innovation on balanced scorecard (BSC) among Malaysian small and medium enterprises (SMEs). Internationalisation covers the dimensions of knowledge, trust, commitment and opportunity development, which can benefit the firm performance in Malaysia by increasing the involvement of SMEs in international business activities. A sample of 202 firms was considered for this study and Structural Equation Modelling (SEM) was used. The dimensions of knowledge, trust, commitment and opportunity development were observed to examine the proposed hypotheses. The results indicate that internationalisation as a whole; such as knowledge, trust, commitment and opportunity development played an important role in innovation and balanced scorecard among Malaysian SMEs. However, this also can solve the existing myth of a role in the internationalisation on innovation towards a balanced scorecard of SMEs in Malaysia because family businesses are a critical pillar of many Malaysian enterprises. Therefore, this research conveys an understanding to the owners and managers to quickly achieve innovation and balanced scorecard results. Finally, this study brings some conclusions to the policy makers and regulators as well.